Answer:
The factors of
is ((x+y)-5)(2x+2y+1)
Explanation:
Given polynomial
=>
![2(x+y)^2-9(x+y)-5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hsnbzqejrpf6xtsao9pm5ayd3v0qqpyred.png)
To Find:
The factors of the polynomial =?
Solution:
Lets assume k = (x+y)
Then
can be written as
![2k^2-9k-5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/95k4qy821ule85b90g41f810gstn8rsjr9.png)
Now by using quadratic formula
k =
![(-b\pm√((b^2-4ac))/(2a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/yaljl1onlm0ee0arjhwpdti5ih4c1kypmo.png)
where
a= 2
b= -9
c= -5
Substituting the values, we get
k =
![(-b\pm√((b^2-4ac)))/(2a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/bez4tx64g7t8afpllxfb69iqx5h0siai7d.png)
k =
![(-(-9) \pm √(((-9)^2-4(2)(-5)))/(2(2)))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/crf43bdmb8p6u3p04hnxx4wljrqk8ctwyd.png)
k =
![(-(-9) \pm √((81+40)))/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jw5nd3cvlhmsssdzdfqx5e9ovl21847gdj.png)
k =
![(-(-9) \pm √((121)))/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/25px3ejw9yo6ljrdwigac8u0zllqng6klk.png)
k =
![\frac{-(-9) \pm 11}}{4}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ducdsqa2lo7vdrcrl7b1x4lek77u6yck0j.png)
k=
![( 9 \pm 11)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/o339vr2buqs1xf37b0wkx43gu6t1wj4vg4.png)
k =
k =
![k_2 = -(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/nze2np8vel8eawj214grozm01ulbp87tu9.png)
![2k^2-9k-5= 2(k-5)(k+(1)/(2))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/o6g9gzly3msc7en3z5oxky77qo9z19eu3q.png)
Solving the RHS we get
![(2)/(2)(k-5)(2k+1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mnohirurtwt0sa6g552j3wibhy6femnvr3.png)
![(k-5)(2k+1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6dbqdhl1o4wdwt99juv0ck5ysh7gp4ca5v.png)
Substituting k = x+y
![((x+y)-5)(2(x+y+1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/q95dsgc3mz0p0scwg57qa4d590jcszjaa4.png)
![((x+y)-5)(2x+2y+1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/3vi8p1uqbye1otftkxmspq0wjxjj747mvb.png)